The Importance of Pre-Tournament Psychological Training of Players - Ikramov Amirbek Aminovich; Luqmonov Subhonjon Shavqiddin og‘li (International Journal on Economics, Finance and Sustainable Development, 2021)
This article highlights the importance of psychological training for athletes in sports games, in particular football, and its impact on result.